Dentes decíduos bovinos podem substituir os dentes decíduos humanos em testes de resistência de união? - Fröhlich, Tatiana Tambara (2017)
The evaluation of the performance of adhesive systems in enamel and dentin of primay teeth is justified by the differences in composition and micromorphology of these compared to permanent teeth. The difficulty of obtaining primary teeth in conditions to be included in laboratory studies causes other substrates to be used as substitutes. The objective of this study was to evaluate the bond strength of adhesive systems to the enamel and dentin of human and bovine primary teeth, in order to answer the research question: can bovine primary teeth replace humans in bond strength studies? 56 sound primary molars and 56 primary bovine incisors were randomly distributed into eight groups (n = 7) for each substrate. Composite resin cylinders (0.72 mm²) were built on the substrates after application of adhesive systems (Single Bond Universal, self etching and acid etching, Clearfil SE Bond and Adper Single Bond Plus) and the specimens submitted to the 24 hour micro-shear test. The values of bond strength (MPa) were submitted to two-way analysis of variance and Tukey's test (α = 0.05). A specimen of each type of tooth was prepared for scanning electron micrograph (SEM) and spectroscopy of Energy dispersive X-rays (ESD). The enamel bond strength values were not significantly influenced (p = 0.97) by tooth type. However the adhesive system interaction vs tooth type was (p = 0.04). In dentin, lower bond strength values (p = 0.03) were obtained for bovine teeth. No significant differences were found for the interaction between adhesive system and tooth type (p = 0.84).When analyzed the adhesive system factor in enamel and dentin, regardless of the factor tooth type, statistically significant difference was found in both substrates. In enamel, the Universal Single Bond adhesive system in the previous acid conditioning strategy presented the same performance as its Single Bond Plus control, since the self-etching strategy was not enough to match its Clearfil SE Bond control. In dentin the adhesive systems presented the same behavior, except for the Single Bond Plus adhesive system that obtained the lowest values of bond strength. For the Universal Single Bond adhesive system the use strategy did not influence the results in both substrates. Bovine and human enamel showed a similar structure of enamel prisms and Ca and P concentration. In dentin, a lower tubular density and Ca and P concentration is obtained in primary bovine teeth. In view of the differences found in the dentin substrate, the replacement of primary human teeth by primary bovine teeth in bond strength studies is only valid when the substrate of interest is the enamel.